2014
DOI: 10.14710/ijred.3.2.75-81
|View full text |Cite
|
Sign up to set email alerts
|

Tin (II) Chloride Catalyzed Esterification of High FFA Jatropha Oil: Experimental and Kinetics Study

Abstract: Biodiesel is one of the promising energy source alternatives to fossil fuel. To produce biodiesel in a more economical way, the employment of the low-cost feed stocks, such as non-edible oils with high free fatty acid (FFA), is necessary. Accordingly, the esterification reaction of FFA in vegetable oils plays an important role in the biodiesel production. In this work, esterification of FFA contained in Crude Jatropha Oil in the presence of tin (II) chloride catalyst in a batch reactor has been carried out. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The simulation of FFA esterification of mixed non-edible oil using RD column in the presence of tin (II) chloride catalyst was carried out using ASPEN PLUS V8.8. The parameters for steady-state simulation which were exhibited in Table I and Table II were established based on the previous experiment performed by Kusumaningtyas et al (2014). Feed compositions for inlet feed are shown in Table 1.…”
Section: Steady-state Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulation of FFA esterification of mixed non-edible oil using RD column in the presence of tin (II) chloride catalyst was carried out using ASPEN PLUS V8.8. The parameters for steady-state simulation which were exhibited in Table I and Table II were established based on the previous experiment performed by Kusumaningtyas et al (2014). Feed compositions for inlet feed are shown in Table 1.…”
Section: Steady-state Simulationmentioning
confidence: 99%
“…k 0i and E ai is the pre-exponential factor and activation energy for the kinetic reaction. The reaction rate constants and activation energy values are presented in Table 3, referring to the data obtained in our previous work (Kusumaningtyas et al, 2014).…”
Section: Steady-state Simulationmentioning
confidence: 99%
“…Figure 5 compared the FFA conversion resulted by reactive distillation and batch process for jatropha oil esterification employing 10% concentration of tin(II) chloride catalyst, which were conducted at 60 °C at various molar ratio of reactants. The experimental data of the batch process was taken from the literature [10]. It was revealed that performance of the reactive distillation process at this condition was constantly superior to that of the batch process.…”
Section: Comparison Between Reactive Distillation and Batch Processmentioning
confidence: 99%
“…SnCl2 could be reused several times, with the same degree of activity. Considering those ad-vantages, tin(II) chloride catalyst was selected for improving the reaction rate of high FFA jatropha oil esterification in this work [10].…”
Section: Introductionmentioning
confidence: 99%
“…Marchetti et al (2007) studied esterification in frying oil using Dowex based basic resins reporting conversion of 80%. Work on tin (II) chloride catalysed FFA esterification in crude jatropha oil was reported by Kusumaningtyasa et al (2014) at 40-60 °C for 4 hours with Alc to oil ratio of 15:1 to 120:1 and 2.5 to 15% w/w of catalyst wrt to oil. Silica sulfuric acid (SSA) and Taguchi orthogonal array method was used by Shah et al (2014).…”
Section: Introductionmentioning
confidence: 99%